A Baseband Signal Processing Scheme for Joint Data Frame Synchronization and Symbol Decoding for RFID Systems. (2010) - Wang Wang, Yung-Yi Yung-Yi; Chen Chen, Jiunn-Tsair Jiunn-Tsair
Abstract : We proposed a novel Viterbi-based algorithm using jiggling substates for joint data sequence detection, symbol boundary self-calibration, and signal frame synchronization for the EPC-Global Gen-2 system. The proposed algorithm first represents the data-encoded scheme as a trellis diagram, and then, as a consequence; the data sequence estimation can be carried out through the Viterbi algorithm. Moreover, time duration of the symbol waveform is iteratively adjusted to generate two substates in the Viterbi algorithm so as to trace and calibrate the symbol boundary on the fly. Compared with conventional approaches, the proposed Viterbi-based algorithm can significantly improve the system performance in terms of data detection accuracy due to its full exploitation of the baseband signal structure combining with the developed substate technique.